Interference of Hsa_circ_0003928 Alleviates High Glucose-Induced Cell Apoptosis and Inflammation in HK-2 Cells via miR-151-3p/Anxa2 - An L (Dove Medical Press, 2020)
Ling An,1,* Dongde Ji,2,* Wenbo Hu,1 Jianrong Wang,1 Xiuzhen Jin,3 Yunfei Qu,4 Ning Zhang5 1Department of Nephrology, Qinghai Provincial People’s Hospital, Xining 810007, People’s Republic of China; 2Department of Gastroenterology, Qinghai Provincial People’s Hospital, Xining 810007, People’s Republic of China; 3Department of Nursing, Qinghai Institute of Health Sciences, Xining 810007, People’s Republic of China; 4Department of Cardiovascular Surgery, Chongqing University Three Gorges Hospital, Chongqing 404000, People’s Republic of China; 5Department of General Practice, Chongqing University Three Gorges Hospital, Chongqing 404000, People’s Republic of China*These authors contributed equally to this work.Correspondence: Yunfei Qu; Ning ZhangChongqing University Three Gorges Hospital, No. 165, Xincheng Road, Wanzhou District, Chongqing 404000, People’s Republic of ChinaEmail yunfeiqu0521@163.com; zhangnning667@163.comBackground: Diabetic nephropathy (DN) is a severe end-stage kidney disease developed from diabetes mellitus. The involvement of circular RNA (circRNAs) in the regulation of DN pathogenesis has been implied, but the underlying mechanism of DN is still lacking. This study aimed to investigate the effect of hsa_circ_0003928 on the inflammation and apoptosis of high glucose (HG)-induced renal tubular cells.Methods: The expression of hsa_circ_0003928, miR-151-3p and Anxa2 in blood samples from DN patients and healthy controls was detected by RT-qPCR. Human renal epithelial cells HK-2 were incubated with D-glucose (30 mmol/l) to establish DN model in vitro. RT-qPCR analysis confirmed the transfection effects and detected the expressions of TNF-α, IL-6 and IL-1β. Western blotting analysis determined the protein expression of Anxa2, Bcl-2, Bax, cleaved caspase-3 and caspase-3. The production of ROS was detected by DCF-DA method and production of inflammatory cytokines was verified by ELISA assay. CCK-8 assay and TUNEL assay were performed to determine cell viability and apoptosis, respectively. Dual-luciferase reporter assay was performed to confirm the relationship between miR-151-3p and hsa_circ_0003928 or Anxa2.Results: Hsa_circ_0003928 and Anxa2 mRNA levels were increased, whereas miR-151-3p was decreased in both HG-induced HK-2 cells and patients with DN. Hsa_circ_0003928 knockdown could decrease cell viability loss and apoptosis, increase Bcl-2 expression, and decrease Bax and cleaved caspase-3 expression. Besides, hsa_circ_0003928 knockdown suppressed HG-induced overproduction of ROS, TNF-α, IL-6 and IL-1β. However, the effects made by miR-151-3p inhibition were opposite to those made by hsa_circ_0003928 knockdown. Furthermore, the binding sites between miR-151-3p and hsa_circ_0003928 or Anxa2 were predicted and verified. Protein expression of Anxa2 was suppressed by hsa_circ_0003928 knockdown, which was rescued by miR-151-3p inhibition.Conclusion: These results demonstrated that hsa_circ_0003928 could act as a sponge of miR-151-3p and regulate HG-induced inflammation and apoptosis partly through regulating Anxa2.Keywords: diabetic nephropathy, hsa_circ_0003928, miR-151-3p, Anxa2